Forming regularity of Mo–Re alloy powders by cold isostatic pressing - HE Haoran; LIU Qi; BO Xinwei; WANG Xiaoyu; YAO Zhiyuan; HAN Xiaoyu; Wang Yujin (Fenmo yejin jishu)
The cold isostatic pressing of Mo–47.5%Re alloy powders (mass fraction) mixed by ball milling and plasma spheroidization was compared and analyzed. The compression parameters were fitted and the relationship between pressing pressure and billet density was analyzed by Huang Peiyun’s double logarithmic pressing theory. The results show that the axial shrinkage of the compacts mixed by both ball milling and plasma spheroidization is greater than that of the radial shrinkage after cold isostatic pressing in the mold with large length/diameter ratio. The billets pressed by plasma spheroidization alloy powders are complete and uncracked, the density changes less along the axial direction, and the core density is slightly lower than that at both ends. The billets pressed by ball milling alloy powders are broken like bamboo joint, the density varies greatly along the axial direction, and the core density is significantly lower than that at both ends. The harding exponent of plasma spheroidization alloy powders is slightly higher than that of ball milling alloy powders, while the pressing modulus (M) is lower than that of ball milling alloy powders, which means the hardening tendency of plasma spheroidization alloy powders is greater.